The Impact of Hosting and Organizing Sporting Events: The 25th Arabian Gulf Cup Football Championship in Basra, Iraq, 2023 as a Model - Saleh, Husam Malik (JURNAL PENDIDIKAN OLAHRAGA, 2025)
The paper aimed to identify and analyze the political, economic, social, cultural, civilizational, geographical, media, and marketing impacts that resulted and improved as a result of hosting this tournament. It also assessed the level and degree of its contribution to promoting and improving growth at the local and national levels, strengthening Iraqi national identity, and opening up to the Gulf, international, and Arab levels. The paper highlighted the importance of focusing on the impact of the sports sector as a tool for comprehensive improvement of the country and soft diplomacy, particularly how a sporting event can contribute to changing the image of an entire country and repositioning it in its regional and global context. It also examined how its impact transcended geopolitical borders. The research question explored the reasons that led Iraq to host the 25th Arabian Gulf Cup Football Championship in Basra in 2023, and how this competition was invested in various aspects: political, economic, social, marketing, media, cultural, civilizational, and geographical. The research hypothesis demonstrated that hosting the Arabian Gulf Football Championship came with incentives, motivations, and reasons of a comprehensive and integrated strategic nature, with the aim of achieving an effective and positive impact with multiple dimensions and conveying a bright and positive image of Iraq. The study's timeframe spanned the period before 2022 and beyond 2023. The spatial boundary was represented by the Iraqi city of Basra, which hosted the championship. Descriptive analysis, a mixed quantitative and qualitative approach, and a case study approach were used. The study concluded that this championship is a success for sports diplomacy, as the competition embodied a tool and means for rapprochement at the political level between the Republic of Iraq and the Gulf states and for clearing the international and regional atmosphere, which enhanced the country's image as a safe and capable state. It recommends finding clear and explicit ways and means to sustain the championship's economic, cultural, and social impact through major activities, and to integrate the national and Gulf private sectors to preserve its legacy in the long term.